Feasibility of same day surgery for pediatric second branchial cleft anomalies. (December 2020) - Pool, Christopher; Ehret, Christopher; Engle, Linda; Zhu, Junjia; Wilson, Meghan N
Abstract: Objective: The risk of expansile hematoma and airway compromise following neck surgery have been used to validate overnight observation. We investigated the outcomes of pediatric patients undergoing a removal of second branchial cleft anomalies (BCA) via either same day surgery or overnight observation. Methods: A retrospective review of patients undergoing second BCA removal between January 1, 2008 to January 1, 2019 was performed. 40 cases were identified for review. Bivariate analyses were performed to determine predictive factors for overnight admission as well as associations between overnight observation and adverse outcomes (hematoma, seroma, airway compromise, infection). Factors evaluated for analysis included ASA class, surgeon type, history of pre-operative infection, recurrent case, operation >90 min, pharyngeal violation, intraoperative cyst rupture, cyst size, and drain placement. Results: There were no life-threatening adverse events. Same day discharge was not associated with adverse events (p = 0.24). Overnight observation was associated with a history of preoperative infection (p = 0.003), cyst > 3.0 cm (p = 0.046), operative time > 90 min (p < 0.001), and drain placement (p = 0.001). There was no association between other investigated variables and adverse events or overnight stay. Conclusion: Same day discharge following second branchial cleft anomalies appears safe and feasible. Further study is needed to determine the safety profile of same day discharge and etiologies of practice patterns of overnight observation.